1999
DOI: 10.1086/307748
|View full text |Cite
|
Sign up to set email alerts
|

Projection, Spatial Correlations, and Anisotropies in a Large and Complete Sample of Abell Clusters

Abstract: An analysis of R ≥ 1 Abell clusters is presented for samples containing recent redshifts from the MX Northern Abell Cluster Survey. The newly obtained redshifts from the MX Survey as well as those from the ESO Nearby Abell Cluster Survey (ENACS) provide the necessary data for the studied Abell cluster datasets is not present in our samples. There are, however, indications of residual anisotropies which we show are the result of two elongated superclusters, Ursa Majoris and Corona Borealis whose axes lie near t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 61 publications
10
52
0
Order By: Relevance
“…Comparing the r 0 value obtained with those found using other low‐redshift cluster samples shows good agreement, e.g. r 0 = 26.0 ± 4.5 Mpc h −1 (Borgani, Plionis & Kolokotronis 1999), 19.4 ≤ r 0 ≤ 23.3 Mpc h −1 (Miller et al 1999), 18.8 ± 0.9 Mpc h −1 (Collins et al 2000). See Nichol (2001) for a good review of r 0 values for various cluster samples.…”
Section: Correlation Functionsupporting
confidence: 56%
“…Comparing the r 0 value obtained with those found using other low‐redshift cluster samples shows good agreement, e.g. r 0 = 26.0 ± 4.5 Mpc h −1 (Borgani, Plionis & Kolokotronis 1999), 19.4 ≤ r 0 ≤ 23.3 Mpc h −1 (Miller et al 1999), 18.8 ± 0.9 Mpc h −1 (Collins et al 2000). See Nichol (2001) for a good review of r 0 values for various cluster samples.…”
Section: Correlation Functionsupporting
confidence: 56%
“…Historically, cluster richness has been described using the Abell richness class (ARC), first defined by Abell (1958). Several studies have shown that the Abell richness parameter is not a welldefined quantity and is subjected to numerous observational biases, including projection effects (e.g., Lucey 1983;van Haarlem et al 1997;Miller et al 1999). For our cluster sample, we have elected to use the parameter B gc (Yee & López-Cruz 1999;Yee & Ellingson 2003) to characterize optical cluster richness.…”
Section: Optical Cluster Richnessmentioning
confidence: 99%
“…The extent of these effects is also surprisingly unknown; measures of completeness and contamination in the Abell catalog disagree by factors of a few. For instance, Miller et al (1999) claim that under-or overestimation of richness is not a significant problem, whereas van Haarlem, Frenk, & White (1997) suggest that one-third of Abell clusters have incorrect richnesses, and that one-third of rich (R ! 1) clusters are missed.…”
Section: Limitations Of Existing Catalogsmentioning
confidence: 99%
“…The largest study of R ! 1 clusters (Miller et al 1999) suggests projection effects are not of great concern for the Abell catalog; however, completeness cannot be gauged without deeper samples. Unfortunately, some of these problems will plague any optically selected cluster sample, including our own, but objective selection criteria and a strong statistical understanding of the catalog can mitigate their effects.…”
Section: Limitations Of Existing Catalogsmentioning
confidence: 99%